From bidirectional pathophysiology to integrative therapeutics: current status and future perspectives of acupuncture for tinnitus-insomnia comorbidity - Hu, Hantong; Huang, Xiaohan; Wang, Yang; Li, Yang; Fang, Lianqiang; Zhou, Jie; Gao, Hong (Frontiers in Psychiatry, 2025)
This perspective article discusses the complex bidirectional relationship between tinnitus and insomnia, a prevalent and burdensome comorbidity. It synthesizes evidence suggesting the conditions mutually exacerbate one another through shared pathophysiological mechanisms, including central hyperarousal, emotional dysregulation, and aberrant neural network connectivity. Our study then explores acupuncture as a potential integrated therapy. Preliminary clinical studies indicate acupuncture can concurrently alleviate both tinnitus and insomnia symptoms. Its therapeutic potential is attributed to multi-target effects, such as regulating the autonomic nervous system and HPA axis, modulating neurotransmitters and neuroinflammation, and normalizing functional brain networks. Our study concludes by highlighting the critical need for rigorous research focusing specifically on the comorbidity to validate these mechanisms and establish clinical efficacy.